2020
DOI: 10.1515/opag-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Decentralised sweetpotato (Ipomoea batatas) vine multiplication in Lake Zone, Tanzania: Five years later

Abstract: Farmer-based seed multiplication is widely promoted by development practitioners, but there is limited understanding of the individual or collective motivations of farmers to engage or disengage in specialised seed production. The objective of this study is to understand the factors influencing the continuity of sweetpotato vine multiplication enterprises in the Lake Zone of Tanzania, five years after support from a project ended. A total of 81 out of 88 trained group or individual decentralised vine multiplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This case study was part of a wider study conducted in 2017–2018 to follow up DVMs in Lake Zone, Tanzania, five years after a project intervention ended (McEwan et al, 2017 ; 2020 ). The broader study used mixed methods with field-based household interviews, plot observations and Focus Group Discussions (FGDs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This case study was part of a wider study conducted in 2017–2018 to follow up DVMs in Lake Zone, Tanzania, five years after a project intervention ended (McEwan et al, 2017 ; 2020 ). The broader study used mixed methods with field-based household interviews, plot observations and Focus Group Discussions (FGDs).…”
Section: Methodsmentioning
confidence: 99%
“…The vines are often considered a common good that are shared freely with kin and neighbors. However, purchase is common at the start of the rains and exchange modalities vary depending on the social relationship and geographical distance between the seed producer and user (McEwan et al, 2020). Surveys have reported that farmers consistently state the lack of adequate quantities of planting material at the start of the rains as a constraint (Barker et al, 2009;Gibson et al, 2009;Kapinga et al, 1995;Sindi et al, 2011).…”
Section: Sweetpotato Seed Production In the Lake Zone Tanzaniamentioning
confidence: 99%
“…This channel appears to work rela�vely well for commercially grown vegetables, soybeans and hybrid maize. However, for other open-pollinated and vegeta�vely propagated crops, except for potato, the private sector has shown very litle interest in the delivery of these crops (Sisay et al 2017;McEwan et al 2020;Mausch et al 2021).…”
Section: Private Sector Deliverymentioning
confidence: 99%
“…Similarly, seeds of minor crops have not been able to reach the shelves of these distributors. For vegetatively propagated crops (VPCs), a route via decentralised multipliers, mostly farming households trained in specialised seed practices and promoted as private sector entrepreneurs, is being pursued (Kilwinger et al, 2021; McEwan et al, 2021), but so far without sustained success (Almekinders et al, 2019a; McEwan et al, 2020). For less commercial crops such as sorghum, which tends to be grown in marginal areas in eastern Africa, new or improved varieties remain largely unadopted (ASARECA/KIT, 2014; Hambloch, Kahwai, and Mugonya, 2021; Kiambi and Mugo, 2016; Mubangizi et al, 2012), except for some cases in which demand from breweries is a major driver.…”
Section: The Underappreciated Problem: Contexts Farming Household Heterogeneity and Seed Systemsmentioning
confidence: 99%